SIMULASI ALIRAN PASIEN RAWAT INAP UNTUK MENGURANGI BOTTLENECK - Thomas Sonny Soegiharto dan Anna Maria Sri Asih (Universitas Gadjah Mada, 2014)
Bottleneck is possible to occur in a system like hospital, especially in admission and discharge of inpatientprocesses. It can have impact on increasing waiting time and delayed time. Some alternatives were proposed toreduce them, i.e. shift scheduling and human resource allocation. This research modelled real system accompaniedby two scenarios: the first scenario was conducted by balancing human resource utility without altering numberof employees, whereas the second scenario considered possibility of changing number of employees. The resultsshowed that both scenarios produced reduction of waiting time and delayed time. The first scenario is more feasiblecompared to the second as no hiring or firing employees occurred, resulting in waiting time reduction of 110.6minutes (15%) and decrease in delayed time by 184 minutes (15.9%). The reduction of waiting time and delayedtime is higher in scenario 2, which are 423.6 minutes (57%) and 281 minutes (24%), respectively. However, theremust be 4 additional employees hired in pharmacy applied in scenario 2.